Avifauna Condition in the K.G.P.A.A Mangkunagoro I Karanganyar Forest Park Utility Block Area - Akbar, Muhammad Rihzalul; Putra, Rizki Andika; Prihadi, Marcellina Ananda; Kusumo, Yuswo Jati; Sefriyani, Veni Elisa; Adiningtyas, Dhana Puspita; Ardiansah, Aam Riawan; Kesuma, Gilang Arga; Nurjuita Nayasilana, Ike (Universitas Jambi, 2024)
The existence of Avifauna in Tahura KGPAA Mangkunagoro's I good habitat conditions supports me. Geographically Tahura is located in Karanganyar, Central Java. This study aims to determine the existence of avifauna in the last 2 years in terms of diversity as supporting information in the development of ecotourism. This research was conducted in August 2023 by comparing data in 2021, using line transect and point count methods. The results showed that the species in Tahura Mangkunagoro I were in the LC (Least Concern) category. the species diversity index (H') was classified as medium (H'=2.744 - 3.106), the evenness index (E) was high (E = 0.842 - 0.888), and the species richness index (R) was high (R = 5.689 - 6.979). Avifauna in Tahura KGPAA Mangkunegoro I is thus important information in supporting the governance and management of the area, especially in the development of ecotourism.